استدعاء الشخصيات التراثية في شعر نزار قباني - يسير خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول البحث موقف نزار قبَّاني من التراث، واستدعاءه لشخصياته، التي تنوَّعت بين شعريَّة، ودينيَّة، وعامَّة، وقد أظهر أنَّ هذه الشخصيات ارتبطت بموضوعين رئيسين: هما المرأة، والوطن، ووظِّفت لخدمتهما، ثمَّ بيَّن بعض المزالق التي وقع الشاعر فيها حين استدعى هذه الشخصيات في شعره. The research deals with poet Nizar Kabbani’s view of the heritage, and his mentioning of its characters that varied between poetic, religious and general. The research shows the correlation of these characters with to major subjects: Woman and homeland. The poet employed his mentioning of these characters in the service of both the subjects. The research shows some pitfalls in which he fell when he recalled these characters in his poetry.